Food Insecurity Screening and Referral Practices of Pediatric Clinicians in Metropolitan Washington, DC - Kofi Essel; Michael Burke; Laura Fischer; Mark Weissman; William Dietz (MDPI AG, 2024)
Background/Objectives: In 2022, 17.3% of US households with children experienced food insecurity (FI). The objective of this study was to examine pediatric clinicians' FI screening and management immediately following the release of the American Academy of Pediatrics (AAP) 2015 FI Policy Statement. Methods: Data were collected in 2016 from 85 primary care pediatric clinicians via an online survey of clinicians in the Washington, DC metropolitan area. Descriptive statistics were calculated using univariate/bivariate analyses. Fisher's exact test and Chi-square tests were used to explore the association between FI screening, health insurance, and clinician demographics. Results: Sixty-six percent of clinicians indicated that they infrequently screened for FI. Only 13% of clinicians used a standardized FI screening tool. Forty-five percent of clinicians screened for FI only when they perceived an acute concern. About 70% of them screened for FI when a patient presented with poor weight gain or was underweight. Conclusions: Immediately after the release of the AAP Policy Statement, it was found that few pediatric clinicians appropriately and frequently screened for FI in our regional sample. Our data emphasize the common misconceptions held by clinicians around FI and the necessity to incorporate training that underscores the invisibility of FI along with effective techniques to screen and intervene.